Emerging Mycotoxins in Aquaculture: Current Insights on Toxicity, Biocontrol Strategies, and Occurrence in Aquafeed and Fish - Patrizio Lorusso; Giusy Rusco; Alessio Manfredi; Nicolaia Iaffaldano; Angela Di Pinto; Elisabetta Bonerba (Toxins, 2025)
Mycotoxins are secondary metabolites produced by various fungal species that can contaminate food and feed, posing significant risks to human and animal health. In aquaculture, the replacement of fishmeal with alternative protein sources has increased the risk of mycotoxin contamination, becoming a major challenge in fish feed production. Current data highlights that fish are exposed not only to common mycotoxins but also to emerging ones, raising concerns about human exposure through fish consumption. In this review, we draw attention to the toxicity data of key emerging mycotoxins from Fusarium (enniatins, ENNs; beauvericin, BEA) and Alternaria (alternariol monomethyl ether, AME; alternariol, AOH), their occurrence in aquafeeds and in commercially relevant fish species in Europe, and potential biocontrol approaches to prevent/mitigate contaminations. From the present review, it emerged that these mycotoxins exhibit in vitro cytotoxic properties. Their prevalence and concentrations vary widely both among aquafeeds, depending on the sample’s origin, and among fish species. Biocontrol approaches using microorganisms or natural compounds show promise as sustainable solutions to limit contamination. However, further research is essential to address data gaps and to allow for a proper risk assessment and, if necessary, the implementation of effective management measures.